The Effects of Perceived Risks and Perceived Values on Online Purchase Intention: Evidence from Young Consumers in Indonesia - Margono, Aurelia Sheryl; Perwitasari, Nindy Sasabela; Nathaniel, Matthew Alexander; Silalahi, Navratilova Ivita; Istijanto, Istijanto (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339), 2022)
COVID-19 pandemic has given a significant impact to both businesses and consumer behaviours. Not only businesses that have to adapt, consumers from all around the world have changed their behaviour in shopping and fulfilling their needs through online. This study aims to examine the effects of perceive risks and perceived values of young consumers on their intention to purchase online electronic products in Indonesia. The convenient sampling was employed with 314 respondents participating in the current research. Then, this study carried out a quantitative analysis by using statistical methods. Exploratory factor analysis was adopted to confirm the validity of the measuring items. Multiple regression analysis was employed to test the influence of perceived risks and perceived values on online purchase intention. The findings show that product risk and security risk have a significant negative effect on consumers' intention to purchase online products, while the escapism motive and value motive have a significant positive effect on the intention to purchase online products.